X-ray spectropolarimetric characterization of GX 340+0 in the horizontal branch: A highly inclined source? - 'La Monaca, Fabio; Di Marco, Alessandro; Ludlam, Renee M.; Bobrikova, Anna; Poutanen, Juri; Li, Songwei; Xie, Fei (EDP Sciences, 2025)
We report the first detection of X-ray polarization in the horizontal branch for GX 340+0 as obtained by the Imaging X-ray Polarimetry Explorer (IXPE). A polarization degree of 4.3% ± 0.4% at a confidence level of 68% is obtained. This value agrees with the previous polarization measurements of Z-sources in the horizontal branch. The spectropolarimetric analysis, performed using a broadband spectral model obtained by NICER and NuSTAR quasi-simultaneous observations, allowed us to constrain the polarization for the soft and hard spectral components that are typical of these sources. The polarization angle for the two components differs by ∼40°. This result can be explained by a misalignment of the NS rotation axis with respect to the accretion disk axis. We compared the results with the polarization that is expected in different models. Theoretical expectations for the polarization of the disk and the Comptonized components favor a higher orbital inclination for GX 340+0 than 60°, as expected for Cyg-like sources. This is in contrast with the results we report for the reflection component based on the broadband spectrum.